Pengaruh Permainan Target Terhadap Kemampuan Shooting Under Ring Bolabasket Siswa SMP Negeri 35 Makassar - Andi Mas Jaya AM; Juhanis Juhanis (Seminar Nasional LP2M UNM, 2019)
Abstract. This research is a type of quantitative research through a one group pretest-posttest design experimental approach that aims to find out; The effect of the target game on the ability to shoot under the ring basketball in SMP Negeri 35 Makassar students. The population is all students of Makassar 35 Public Middle School. The sample used was grade VII students as many as 30 people. The sampling technique is Proportionv Sampling. Data collection techniques in this study used the test. The instrument used in this study was a performance test for shooting under the basketball ball ring. Data analysis techniques used the t test analysis and had previously been tested for normality and homogeneity through the SPSS 21 program at a significant level α = 0.05. Based on the analysis of the results of research and discussion, it can be concluded that tcount = 4.990> ttable (0.05) = 2.039, the hypothesis is accepted. Thus it can be concluded that there is a significant effect after being given a treatment of the target game on the ability to shoot under the ring in students of SMP Negeri 35 Makassar. The influence is also shown by the posttest average value of 4,560> 2,810 pretest average value Keywords: target game, shooting under the ring, basketball